Preoperative Assessment of Anomalous Right Coronary Artery Arising from the Main Pulmonary Artery - Marshall W. Winner; Subha V. Raman; Benjamin C. Sun; Juan A. Crestanello (Case Reports in Medicine)
Anomalous origin of the right coronary artery from the pulmonary artery is a rare condition. Two cases are presented in this paper. One case was treated by ligation and coronary artery bypass. The other was treated by direct reimplantation of the anomalous coronary artery into the aorta.